Perspectives on Underlying Factors for Unhealthy Diet and Sedentary Lifestyle of Adolescents at a Kenyan Coastal Setting - Ssewanyana, Derrick; Abubakar, Amina; van Baar, Anneloes; Mwangala, Patrick N.; Newton, Charles R. (Frontiers in Public Health, 2018)
Unhealthy diet and physical inactivity are among the key modifiable risk factors for non-communicable diseases, such as diabetes and cardiovascular disease. Although such diseases often only appear in adulthood, these behaviors are typically initiated or reinforced already during adolescence. However, knowledge on underlying factors for adolescents’ unhealthy dieting and physical inactivity in sub-Saharan Africa (SSA) is poor. We conducted in-depth interviews and focus group discussions to explore the perceptions of a diverse group of 78 young people of 10–19 years of age, which also included some adolescents living with HIV, as this is an emerging group in the HIV/AIDS epidemic in many parts of SSA. In addition, 10 stakeholders, such as teachers, clinicians, and staff from organizations at the Kenyan coast and seven young adult community representatives informed us on: (a) adolescents’ unhealthy food choices and their forms of sedentary behavior; (b) predisposing factors; and (c) protective factors against unhealthy food choices and sedentary behavior of adolescents living in Kilifi County. The findings reveal that adolescents occasionally access nutritious foods, such as fruits, vegetables, and animal protein. However, there is a growing tendency to consume unbalanced diets with high intake of carbohydrates, oily foods, and consumption of sugar dense processed foods and drinks. Sports and domestic chores were found to be major sources of physical activity. Sedentary lifestyles characterized by a long-time sitting and chatting, watching sports games and movies were described. Adolescents living with HIV did not indicate any divergent perceptions from those of other adolescents relating to diet and physical activity, but mentioned health-related conditions, such as medication, asthma, and low body weight, as a risk factors for sedentary lifestyle. Using a Socio-Ecological model, our findings suggest that risk factors are numerous and interrelated, especially at intrapersonal, interpersonal, and community level. The negative influences at an intrapersonal level were as follows: body image concerns, attitudes and misconceptions, substance use behavior, and taste for unhealthy foods. In the interpersonal domain, household poverty and parenting practices that condone unhealthy habits were identified risk factors. Availability of affordable unhealthy foods, high prices for nutritious food, farming practices, gambling, and influx of transportation alternatives in the community were interrelated but also had relationships with intrapersonal and interpersonal risk factors. Modernization and poor implementation of policies were discussed as enabling factors especially by stakeholders from a societal perspective. Seasonality and farming practices, school attendance, community-based services, and regulations mitigating adolescents’ engagement in gambling were identified as potential protective factors. Our findings provide a unique qualitative insight of the factors underlying adolescents’ dietary and sedentary lifestyle and highlight the need for ecological intervention approaches to address these forms of health risk behavior in a rural African setting.